The relationship between sports sponsorship and corporate image, reputation and intention to buy: TORKU case - Abdullah Sencer Temel; Erkan Faruk Sırın (Selcuk University, 2017)
The purpose of this research is to examine the relationship between the recognition (being heard or not) of TORKU's (Konya Seker) sports sponsorships and image, reputation and intention to buy. In addition to this, the effects of the image the customers perceive and reputation on the buying decisions. For this purpose, the data obtained with survey method from 350 customers chosen by random sampling who shop at large shopping malls in Konya province were evaluated by descriptive, correlation and regression analysis. The scales used in the research were prepared by researches on the basis of image perception, reputation perception and intention to buy, and reliability and validity studies were carried out. As a result of the research; image perception and extent of reputation perception and intention to buy between those who heard of TORKU's sports sponsorships and those who didn't have shown the effectiveness of sponsorship activities of TORKU. Consequently, it has been demonstrated that the sports sponsorships have a positive effect on the customers, in particular TORKU customers.